Defining and measuring blood donor altruism: a theoretical approach from biology, economics and psychology. Issue 2 (9th October 2013) - Evans, R.; Ferguson, E.
<x xml:space="preserve">Abstract</x> Background and Objectives While blood donation is traditionally described as a behaviour motivated by pure altruism, the assessment of altruism in the blood donation literature has not been theoretically informed. Drawing on theories of altruism from psychology, economics and evolutionary biology, it is argued that a theoretically derived psychometric assessment of altruism is needed. Such a measure is developed in this study that can be used to help inform both our understanding of the altruistic motives of blood donors and recruitment intervention strategies. Materials and Methods A cross‐sectional survey (N = 414), with a 1‐month behavioural follow‐up (time 2, N = 77), was designed to assess theoretically derived constructs from psychological, economic and evolutionary biological theories of altruism. Theory of planned behaviour (TPB) variables and co‐operation were also assessed at time 1 and a measure of behavioural co‐operation at time 2. Results Five theoretical dimensions (impure altruism, kinship, self‐regarding motives, reluctant altruism and egalitarian warm glow) of altruism were identified through factor analyses. These five altruistic motives differentiated blood donors from non‐donors (donors scored higher on impure altruism and reluctant altruism), showed incremental validity over TPB constructs to predict donor intention and predicted future co‐operative behaviour. Conclusions These findings show that altruism in the context of blood donation is multifaceted and complex and, does not reflect pure altruism. This has implication for recruitment campaigns that focus solely on pure altruism.